DAKWAH DAN SINEMA: INTERPRETASI NILAI-NILAI ISLAM DALAM FILM MIMPI ANANDA RAIH SEMESTA - Efrina, Eti; Tri Handoyo; Rasman; Mukhlizar (Fakultas Agama Islam Universitas Muhammadiyah Bengkulu, 2025)
Film has the power to indirectly influence its audience, both in terms of behavior, attitudes, and the process of personality formation. In Indonesia, various films have been produced, one of which is Mimpi Ananda Raih Semesta (MARS), which won the BISA Hong Kong Film Award in 2017. This film tells the story of the struggles of Tupon and Sekar Palupi, two female figures from Gunung Kidul, Yogyakarta. Through various scenes in the film, a variety of implied dakwah values can be found. The aim of this research is to identify the dakwah values contained in the film. The method used is content analysis based on Krippendorff's theory, which consists of six stages: unitizing, sampling, coding, data reduction, drawing conclusions, and narrative construction. This research is a library research with a descriptive qualitative approach. The data sources are derived from scenes in the film MARS, supported by literature such as books, journals, and other relevant sources. The results of this study show that there are 12 scenes that contain dakwah elements, consisting of two scenes with values of aqeedah, two scenes with values of sharia, and eight scenes with values of akhlak. Based on this analysis, it can be concluded that this film predominantly conveys dakwah messages through akhlak values. Keywords: Analysis, Da'wah Values, MARS Film